Experimental study of bending interface characteristics of CFRP-strengthened long-span steel main beams at different temperatures. (15th May 2021) - Teng, Rumin; Guo, Yongchang; Wang, Hongyu; Zhao, Zhe; Wang, Xin
Highlights: Verify the feasibility and effectiveness of the CFRP reinforcement by scale models. Study the stress distribution of beam bending interface at different temperatures. It is better to repair the long-span steel girder by CFRP in the normal environment. Rubber layer's insulation and protection is main factor to the CFRP's effectiveness. Raising the CFRP's thickness can reduce temperature's impacts on the repair effect. Abstract: The deterioration of steel beams presents a severe safety problem in large shipbuilding gantry cranes. The fibre-reinforced polymer (FRP) strengthening technique is commonly used to solve this problem. In current research, the influence of carbon FRP (CFRP) on the flexural strength of large crane steel beams is experimentally studied using scale models of beams to determine the bond interface characteristics of CFRP. In this work, the stress distribution on the bending interface of a main steel beam is investigated under different environmental temperatures. The results show that the bending capacity of long-span steel main beams is improved by CFRP. The experimental results also indicate that insulation and protection of the rubber layer are important factors in the effectiveness of CFRP.